APLIKASI CABINET DRYER (PENGERING KABINET) UNTUK MENINGKATKAN PRODUKSI BAHAN BAKU PENGAWET ALAMI BUAH KECOMBRANG (Etlingera elatior) - Rifda Naufalin; Rumpoko Wicaksono; Poppy Arsil (Dinamika Journal : Pengabdian Masyarakat, 2019)
The development of public awareness of food safety has led to the  demands from people who want more natural food.  these conditions provide new opportunities to develop and produce natural preservatives plants namely kecombrang.  This campus intellectual product development business program (PPUPIK) aims to increase the production of quality natural preservatives made from kecombrang fruit in order to support food security.  the method used is the prototype dryer application so it is ready for commercial use.  PPUPIK activities can produce natural preservatives made from kecombrang fruit with consistent quality, increased production capacity and increase the efficiency of raw materials.Keywords: nature preservative, cabinet dryer, kecombrang fruit